WHAT OF THE APPRAISER? - Olson, Lyle H. (The Accounting Review, 1932)
Modern business methods and requirements resulting from the complex and diversified properties comprising the fixed assets of large corporations, have developed appraisal organizations to serve in broader geographical areas, for larger units and groups of properties, with greater responsibility, authority and public recognition, and to supplement the service of the individual specialist with the broader experience, coordinated effort, and uniform principles, possible from large coöperative organizations. The investment in the properties may be measured on the basis of the original investment representing the actual expenditures made at the time properties were acquired, constructed or equipped, an average investment representing what the property would have cost at prices at the given time or over an average period of years that may be estimated for the purpose of computation and the normal investment represented by the cost of reproduction as of a specified date. In order to have a basis for uniform measurements, there must be a fixed standard. This fixed standard is the cost of reproduction new. The cost of reproduction new represents a determinable fact that can be applied consistently and effectively to all properties.